Innovative Approaches in Citizenship Education Research: Conceptual Perspectives and Ethical Cautions - Matusevych, Tetiana; Zadorozhna, Olga (Studia Warmińskie, 2023)
This article is devoted to the analysis of innovative approaches in citizenship education research taking into account conceptual perspectives and ethical cautions. The conceptual, axiological, and ethical basis of such innovative frameworks as digital citizenship education and artificial intelligence application for the development of responsible citizenship is elaborated. These innovations revolutionized the theory and practice of citizenship education, causing the use of new approaches and pedagogical methods as well as change in learning environments simultaneously adding new modalities and domains into objectives of citizenship education.